Polytetrafluoroethylene covered stents during PCI: Wanting more from our "savior". Issue 4 (10th October 2019) - Seth, Ashok; Singh, Vivudh Pratap
Key Points: Polytetrafluoroethylene covered stents are life‐saving treatment of coronary artery perforation and effective treatment for coronary artery aneurysm. Procedural and Technical consideration may improve long‐term outcomes. New generation of user friendly covered stents could aid rapid stabilization of patients during coronary artery perforation.